Exploring the Microbiota of Faba Bean: Functional Characterization of Lactic Acid Bacteria - Verni, Michela; Wang, Changyin; Montemurro, Marco; De Angelis, Maria; Katina, Kati; Rizzello, Carlo G.; Coda, Rossana (Frontiers in Microbiology, 2017)
This study investigated the metabolic traits of twenty-seven lactic acid bacteria strains belonging to different species, previously isolated from faba bean. The activities assayed, related to technological and nutritional improvement of fermented faba bean, included peptidases, -glucosidase, phytase, as well as exopolysaccharides synthesis and antimicrobial properties. In addition, the bacteria performance as starter cultures during faba bean fermentation on proteolysis, antioxidant potential, and degradation of condensed tannins were assessed. Fermentative profiling showed that only 7 out of 27 strains were able to metabolize D-raffinose, particularly Leuc. mesenteroides I01 and I57. All strains of P. pentosaceus exerted high PepN activity and exhibited β-glucosidase activity higher than the median value of 0.015 U, while phytase activity was largely distributed among the different strains. All the weissellas, and in lower amount leuconostocs, showed ability to produce EPS from sucrose. Almost all the strains did not survive the simulated gastrointestinal tract with the exception of P. pentosaceus I56, I76, 147, I214, having a viability of 8-9 log CFU/ml at the end of the treatment. None of the strains showed antimicrobial activity towards Staphylococcus aureus, while 8 strains of P. pentosaceus exhibited a strong inhibitory activity towards Escherichia coli and Listeria monocytogenes. Generally, the doughs fermented with pediococci exhibited high amount of total free amino acids, antioxidant activity, and condensed tannins degradation. These results allowed the identification of lactic acid bacteria biotypes as potential starter cultures for faba bean bioprocessing, aiming at the enhancement of faba bean use in novel food applications.